Analysis Of The Application Of Statement Of Financial Accounting Standards 109 At The Amil Zakat Institution Dsni Amanah Muka Kuning Batam - Nisa Ulkhairi; Neni Marlina Br Purba (Enrichment : Journal of Management, 2022)
This study aims to determine the application of zakat accounting on financial Amil Zakat Institution DSNI Amanah Province and to determine the suitability of the application of accounting practices of zakat Amil Zakat Institution DSNI Amanah Province based on PSAK No. 109. The type of research used in this study is a type of qualitative research using an approach descriptive qualitative. Data collection methods used in this study are through literature studies, interviews and documentation. The results of the study concluded that the process of accounting records carried out at the Amil Zakat Institution DSNI Amanah originated from evidence of transactions obtained from the collection, distribution and utilization of zakat funds. The Amil Zakat Institution DSNI Amanah uses a system of recording cash bases and journalizing by applying double entry records. Overall, the Amil Zakat Institution DSNI Amanah Province has not applied accounting practices in accordance with those required by PSAK No. 109, especially in terms of presentation and disclosure. The financial statements made are only in the form of funds cash flow statements and changes in funds reports.